The French Advanced Course for Deployment Surgery (ACDS) called Cours Avancé de Chirurgie en Mission Extérieure (CACHIRMEX): history of its development and future prospects. Issue 5 (13th October 2015) - Bonnet, Stéphane; Gonzalez, F; Mathieu, L; Boddaert, G; Hornez, E; Bertani, A; Avaro, J-P; Durand, X; Rongieras, F; Balandraud, P; Rigal, S; Pons, F
Abstract : Introduction: The composition of a French Forward Surgical Team (FST) has remained constant since its creation in the early 1950s: 12 personnel, including a general and an orthopaedic surgeon. The training of military surgeons, however, has had to evolve to adapt to the growing complexities of modern warfare injuries in the context of increasing subspecialisation within surgery. The Advanced Course for Deployment Surgery (ACDS)—called Cours Avancé de Chirurgie en Mission Extérieure (CACHIRMEX)—has been designed to extend, reinforce and adapt the surgical skill set of the FST that will be deployed. Methods: Created in 2007 by the French Military Health Service Academy (Ecole du Val-de-Grâce), this annual course is composed of five modules. The surgical knowledge and skills necessary to manage complex military trauma and give medical support to populations during deployment are provided through a combination of didactic lectures, deployment experience reports and hands-on workshops. Results: The course is now a compulsory component of initial surgical training for junior military surgeons and part of the Continuous Medical Education programme for senior military surgeons. From 2012, the standardised content of the ACDS paved the way for the development of two more team-training courses: the FST and the Special Operation Surgical Team training. The content of this French military original war surgery course is described, emphasising its practical implications and future prospects. Conclusion: The military surgical training needs to be regularly assessed to deliver the best quality of care in an context of evolving modern warfare casualties.